A fast-blind IP watermark detection scheme based on position fuzzification. (2019) - Huang, Weihong; Li, Renfa; Xu, Jianbo; Huang, Yin; Sheng, Yong
The rapid advancement in internet of things (IoTs) has created new demands for intellectual property (IP) protection. Existing zero-knowledge-based IP watermark detection schemes have low performance in real-time detection. To address this issue, we propose a position fuzzification-based IP watermark detection scheme mainly aiming to reduce the rounds of inquiry. Firstly, a random sequence is produced by chaos system to scramble all the resource positions of an IP design. Then watermark positions are fuzzified to make the scramble algorithm irreversible. A verifier can achieve zero-knowledge proof of IP ownership by one round of inquiry. Experiments show that the proposed scheme can greatly reduce computational complexity during blind IP watermark detection and enhance performance in real-time watermark detection.